Predicting Job Satisfaction Based on Personality Traits and Psychological Empowerment in Employed Middle-Aged and Elderly People - Peyman Hatamian; Mojtaba Ahmadi Farsani (University of Social Welfare & Rehabilitation Sciences, 2019)
Objectives The associated factors with job satisfaction can predict the personal and professional progress of middle-aged and elderly people, as well as their future success. The present study aimed to predict job satisfaction based on personality traits and psychological empowerment among middle-aged and elderly working people. Methods & Materials Of all middle-aged and elderly employed people in Kermanshah City, Iran, a sample of 240 people were selected by the convenience sampling method. The study data were collected using NEO five-factor inventory, short form, psychological empowerment questionnaire and job satisfaction survey. For data analysis, the Pearson correlation coefficient and regression analysis methods were used. Results The results revealed that personality characteristics of extrovertism, accountability and flexibility were positively associated with job satisfaction with correlation coefficients of 0.42, 0.34, and 0.07, respectively. In addition, there was a positive and significant relationship between psychological empowerment and job satisfaction with correlation coefficient of 0.43. However, no significant relationship was found between mental health and pleasure with job satisfaction. Conclusion According to the findings of this study, personality traits and psychological empowerment can predict job satisfaction in middle-aged and elderly people.